Psychology of conflict in drama and poetics of individualized characterization of characters (Eurasian Journal of Philology Science and Education, 2021)
In the research work, the theoretical foundations of the literary only genre of drama genres in the world art of speech (drama, tragedy, comedy), the foundations of the historical and poetic formation of the tradition of artistic continuity in drama are scientifically systematized. The main character of the works of drama, carried out by the integrity of literary creativity and theatrical and stage production, is scientifically formulated. The creative significance of outstanding playwrights in the formation and development of national and world theatrical art in the history of classical drama, whose works were embodied in the integrity of literary and theatrical-stage production, was evaluated. In the composition of plays written on the basis of poetic laws of drama, it is described in detail that the literary poetic character and methods of motor actions (monologues, dialogues, facial expressions, Remarque), stage and technical equipment (mizansena, scenery, makeup of actors, stage clothing, lighting, etc.), the activities of creative personalities (author-playwright, director-director, actor) are carried out in integrity. Shakespeare’s literary activity lasted twenty-two years, of which twelve years are considered the most fruitful. During this time, he writes his highest tragedies from an artistic point of view. The rich-ness of the theme, the clarity of the ideological direction and the deeply realistic expression of everyday events raised Shakespeare’s tragedies to a high level. Therefore, his dramatic work has firmly established itself on the stage of theaters around the world and still excites the audience. And the tragedy of M. Auezov, whose works are in harmony with the examples of classical genres of world civilization, left an imprint on the Kazakh drama of the early XX century, which went through its own stages of development, clearly reflects the poetic and psychological features of socio-psychological conflict (conflict) and individual characterization of characters. Therefore, the tragedies of William Shakespeare’s «Romeo and Juliet» and Mukhtar Auezov’s «Karagoz» in classical drama are a continuation of the artistic tradition. In the drama of these writers, the study of the psychology of conflict and the poetics of individualized characterization of characters will always be an urgent problem.